Editor's Letter 11.4. Issue 4 (23rd January 2020) - Unknown
Abstract : The Editor's letter summarizes the articles published in this issue and calls for readers to submit ideas and articles for future issues. 摘要: 本篇编者按总结了本期发行的文章, 同时向读者就未来期刊内容征集观点和文章。 Resumen: La carta de la editora resume los artículos publicados en este número y llama a los lectores a enviar ideas y artículos para futuros números.